Bay-aminated Octaazaperopyrenedioxides (OAPPDOs) as precursors for Diazepine and Diazepinone derivatives - Eichelmann, Robert; Bender, Kai; Günther, Julius A.; Ziegenhagen, Levi A.; Ballmann, Joachim; Gade, Lutz H. (Organic letters, 2025)
Fully bay-aminated octaazaperopyrenedioxide (OAPPDO) derivatives have been accessible via Buchwald-Hartwig amination of the bay-chlorinated starting material. They were isolated as semiquinoidal species with a bent polycyclic core and characterized as nonfluorescent charge-transfer dyes. The corresponding secondary amines were synthesized by reduction and displayed typical absorption and emission behavior for perylene derivatives. One of the reduced amines served as a precursor for conversion of the secondary amino groups to 1,3-diazepine and -diazepinone units spanning the bay-area - seven-membered ring motifs hitherto unknown in perylene chemistry. The photophysical and electrochemical properties of the azaperylene dyes were investigated by absorption and emission spectroscopy supported by time-dependent density functional theory methods and cyclic voltammetry as well as differential pulse voltammetry.
Gesehen am 10.07.2025